Program Amaliyah Ramadhan dalam Meningkatkan Kepedulian Sosial Santri di Pondok Trensami Kwangsan Sedati, Sidoarjo - Purwanti, Yeni (Lembaga Pengembangan Kinerja Dosen, 2026)
The Amaliyah Ramadhan Program is a religious activity carried out to instill spiritual values ​​while increasing the social awareness of students. This activity serves as a means of character development through various worship and social activities during the month of Ramadan. The implementation of a targeted program is expected to be able to form an attitude of empathy, togetherness, and concern for the surrounding community. This study aims to describe the implementation of the Amaliyah Ramadhan Program in increasing the social awareness of students at Pondok Trensami Kwangsan Sedati, Sidoarjo. The method used is the Asset Based Community Development (ABCD) approach by utilizing the potential and assets owned by the Islamic boarding school community. The stages of the activity include discovery (identifying potential), dream (formulating program expectations), design (planning activities such as tadarus, studies, sharing takjil, and charity), and destiny (program implementation and evaluation). The results of the activity indicate that the Amaliyah Ramadhan Program is able to increase the social awareness of students as demonstrated through active participation in sharing activities, attitudes of mutual assistance, and increased awareness to care for the surrounding community. This program also strengthens the values ​​of togetherness and social responsibility within the Islamic boarding school environment.